2022
DOI: 10.3389/ijph.2022.1604767
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Workers’ Low Knowledge of Female Genital Schistosomiasis and Proposed Interventions to Prevent, Control, and Manage the Disease in Zanzibar

Abstract: Objectives: This study was conducted to explore healthcare workers’ knowledge of female genital schistosomiasis (FGS) and describe proposed interventions to raise awareness about FGS and strengthen healthcare facilities’ capacity to manage FGS cases.Methods: We conducted four cross-sectional focus group discussions and 16 key informant interviews with purposively selected healthcare workers in Zanzibar. Discussions and interviews were digitally recorded, transcribed, and analyzed using NVivo software.Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…The same responses were given by 4% and 21% of the community women, respectively. Similar misconception of sexual transmission of FGS has been reported in studies conducted among local health workers in Zanzibar and Ghana [37,38]. These misconceptions could be linked to confusion, as reported in Ghana, Tanzania and Zanzibar, where the respondents could not clearly distinguish the transmission modes from those of other water-borne diseases and sexually transmitted infections (STI) [32,33,39].…”
Section: Discussionmentioning
confidence: 65%
“…The same responses were given by 4% and 21% of the community women, respectively. Similar misconception of sexual transmission of FGS has been reported in studies conducted among local health workers in Zanzibar and Ghana [37,38]. These misconceptions could be linked to confusion, as reported in Ghana, Tanzania and Zanzibar, where the respondents could not clearly distinguish the transmission modes from those of other water-borne diseases and sexually transmitted infections (STI) [32,33,39].…”
Section: Discussionmentioning
confidence: 65%
“…Additionally, a lack of knowledge of the FGS among HCWs can lead to incorrect diagnosis ( Mazigo et al, 2022b ) and treatment ( WHO, 2015 ). Raising awareness and knowledge about FGS, could help encourage women to seek timely medical care, prevent long term consequences, such as infertility or cancer associated with the disease ( Mazigo et al, 2022a ), and reduce antimicrobial resistance due to inappropriate use of antibiotics ( Nemungadi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Female genital schistosomiasis (FGS) is the chronic manifestation of schistosomiasis induced by a persistent infection with S. haematobium through the deposition and calcification of eggs in the female genital tract ( Mazigo et al, 2022a ). The global burden of FGS is unknown most likely due to under-reporting ( Engels et al, 2020 ), but it is estimated that it affects 40 to 56 million women and girls worldwide ( Hotez et al, 2019a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Despite these efforts, studies have reported inadequate knowledge and skills to manage the disease by health professionals among community members. 24 , 35 , 36 , 37 Because of lack of awareness among affected communities and the insufficient expertise and understanding among medical professionals, FGS is an underreported, misdiagnosed and untreated medical condition. 35 , 38 , 39 The FGS menace cannot be adequately addressed without adequately equipping different cadres of healthcare workers with the knowledge and tools to diagnose and manage the disease.…”
Section: Introductionmentioning
confidence: 99%